Fiscal Decentralization and its Effect on Poverty Alleviation: Case Study of Indonesia - Rima Melati Anggraeni; Mohamad Khusaini; Ferry Prasetyia (Bulletin of Islamic Economics, 2022)
This research provides empirical evidence of the effect of fiscal decentralization on poverty alleviation and used data from 505 districts/cities in Indonesia from 2010 to 2019. The poverty rate is used as an indicator to measure the social condition of the area with the parameter of the percentage of the total population below the poverty line, while the fiscal decentralization indicator uses approach to the size of the ratio of PAD to total regional income and expenditure. The estimated results used the fixed effect model shows that fiscal decentralization have significant role to reduce the level of poverty in districts/cities nationally. From this estimation result, the recommended policy formulation is pro-poor fiscal decentralization through strengthening regional financial capacity, both optimizing Original Local Government Revenue (PAD), allocating Transfer Funds to Regions that are specific grants, improving the quality of spending and regional financial management, as well as mechanisms monitoring - better evaluation. In addition, the effectiveness and efficiency of regional government policies in dealing with socio-economic issues such as unemployment and growth population must also be considered.